Chemical modification of poly(vinyl chloride) for blood and cellular biocompatibility1. Issue 56 (19th June 2015) - Monika; Mahto, Sanjeev Kumar; Das, Snehashish; Ranjan, Amit; Singh, Santosh Kumar; Roy, Partho; Misra, Nira
<x xml:space="preserve">Abstract</x> Poly(vinyl chloride) (PVC) was modified with three different ionomers including thiosulphate, thiourea and sulphite for improving the biocompatibility of the polymer.